ПОРЯДОК ПРИМЕНЕНИЯ МЕРЫ ПРЕСЕЧЕНИЯ В ВИДЕ ЗАЛОГА ПО УГОЛОВНОМУ ПРОЦЕССУАЛЬНОМУ ЗАКОНОДАТЕЛЬСТВУ УКРАИНЫ - ФОМИНА, Татьяна Григорьевна (SUPREMANCE OF LAW, 2016)
The author of the article has defined the procedure of applying interim measures in the form of a bail under the current legislation of Ukraine. The issues regarding the bail’s object, procedural status of a bailor are considered. Separately, the author has studied the procedure for applying a bail as alternatives to detention. Propositions into the criminal procedural legislation of Ukraine have been formulated.